The three dimensional analysis of the Sforzesco brace correction. Issue 2 (October 2016) - Donzelli, Sabrina; Zaina, Fabio; Lusini, Monia; Minnella, Salvatore; Respizzi, Stefano; Balzarini, Luca; Poma, Salvatore; Negrini, Stefano
Abstract Background Scoliosis is a three dimensional deformity, and brace correction should be 3D too. There is a lack of knowledge of the effect of braces, particularly in the sagittal and transverse plane. The aim of this study is to analyse the Sforzesco Brace correction, through all the parameters provided by Eos 3D imaging system. Method Design: This is a cross sectional study from a prospective database started in March 2003. Participants: 16 AIS girls (mean age 14.01) in Sforzesco brace treatment, with EOS x-rays, at start, in brace after 1 month and out of brace after the first 4 months of treatment.Outcome measures: All the parameters and the Torsio-Index obtained from 3D Eos System, in and out of brace, in the three planes. Statistical analysis:the variability of the parameters and the mean differences were analyzed and compared using paired T test. ANOVA was used for multiple comparisons. Critical P value was set at 0.05. Results In the comparison of in-brace vs start of treatment, the mean Cobb angle changed significantly from 36.44 +/− 4 to 28.99 + −3.9° (p = 0.01). Significant changes in all the sagittal parameters were found (p = 0.02). In the axial plane, the Torsio Index changed significantly in-brace for thoracolumbar and lumbar curves (P < 0.05). The analysis of the single vertebral tilt demonstrated that the effect of the brace is mostly concentrated at specific segments: T4-T5, T10-T12, L1 and L5 in the axial plane and T3-T6 and T10-L1 in the frontal plane. Conclusion The Sforzesco brace mostly modifies the middle of the spine and preserves the sagittal balance. The single vertebral orientation in each plane should be considered together with the typically used values to assess brace effect.